Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.
Trending News
x²·4^√(2-x) + 4^(2-x) = 4^(√(2-x)+2) + x²·2^(-2x)?
Here's how it looks in proper notation:
https://dl.dropbox.com/u/17850283/yanswers_equatio...
Please show how you got the solutions.
X and x are the same variable; Yahoo automatically capitalized the first one.
I figured it out myself. If anyone is interested, it's solved by moving the terms with x² as the coefficient on one side and everything else on the other, and then factoring out x² and the 16s you get from 4^(2-x) and 4^(√(2-x)+2).
1 Answer
- MorewoodLv 79 years agoFavorite Answer
So it looks like:
x²·4^√(2-x) + 4^(2-x) = 4^(√(2-x)+2) + x²·2^(-2x)
⇒ x²·4^√(2-x) + 4^(2-x) - 4^(√(2-x)+2) - x²·2^(-2x) = 0 {on one side}
⇒ x²·4^√(2-x) + 16[4^(-x)] - 16[4^√(2-x)] - x²·4^(-x) = 0 {exponent laws}
⇒ x²·4^√(2-x) - x²·4^(-x) + 16[4^(-x)] - 16[4^√(2-x)] = 0 {commutativity}
⇒ x²·[4^√(2-x) - 4^(-x)] + 16[4^(-x) - 4^√(2-x)] = 0 {distributive law}
⇒ (x²-16)·[4^√(2-x) - 4^(-x)] = 0 {distribute law again}
⇒ (x-4)·(x+4)·[4^√(2-x) - 4^(-x)] = 0 {difference of squares}
⇒ x=4 or x=-4 or √(2-x) = -x {with x≤0 since √(...)≥0}
Square both sides of that last equation to get 0 = x² + x - 2 = (x+2)(x-1) ⇒ x=-2. (The x=1 solution to that last equation is extraneous. It does not satisfy the original equation which has only positive square roots.)